Principles to guide research and policy on psychological well-being in remote island developing states in the South Pacific - Orbán, Levente L. (Frontiers in Psychiatry, 2024)
Adverse climatic changes around the globe and predictions of catastrophic and irreversible alteration in global weather patterns, temperature rise, and coast-line habitability require a careful examination of consequences on the resilience and mental health of people who will endure these changes. This paper is concerned with the South Pacific region. This geography has benefited from a relatively stable climate that is seen in the lush and vibrant natural world with many unique species of plants and animals exclusively found here. This paper examines the psychological profile of the people in the South Pacific using an evolutionary framework, and considers their local climate risks and lifestyle patterns with the aim of exploring possible mental health trajectories.